(untitled) (Journal of Pharmaceutical Negative Results, 2022)
OBJECTIVE: The aim of the study is to identify the types of gram-negative bacteria that cause diabetic foot infections in Iraqi patients.METHODS A cross-sectional study has been conducted on surgical operations on the bottom of the foot at Al-Imam Al-Hussein hospital in Thi-qar province, which is one of the southern provinces in Iraq, for the period from March 1st to December 31st, 2020.RESULT: Among gram-negative bacteria, Enterobacter spp. and E. coli were, respectively, the most frequently isolated organisms. The antibiotic meropenem was found to be effective against microorganisms. Imepenem, however, was highly resistant to antibiotics.CONCLUSION: Understanding the bacteriology of diabetic foot infection, as well as its isolation and identification, aids in the selection of antibiotics and the planning of proper diabetic foot infection management.